PROGNOSTIC SIGNIFICANCE OF GALECTIN-3 LEVEL ASSESSMENT IN METABOLIC SYNDROME PATIENTS WITH HEART FAILURE - O. M. Drapkina; R. N. Shepel; T. A. Deeva (Кардиоваскулярная терапия и профилактика)
Aim. To assess the level of galectin-3 in blood serum of metabolic syndrome patients (MS), with heart failure (CHF).Material and methods. Totally, 43 patients investigated, with MS, and of those 37 CHF patients and 33 on-CHF, of those 17 had CHF diagnosed. Galectin-3 level in blood serum was measured by immune enzyme assay.Results. Galectin-3 level in blood plasma of MS patients was significantly higher comparing to the group with no MS — 1,89±1,71 ng/mL and 1,03±0,22 ng/mL, respectively. In the control group maximum galectin-3 level was 1,5 ng/mL, but in MS group 27% had galectin-3 higher than 3 ng/mL. It was found that mean levels of galectin-3 were significantly higher in CHF group (1,73±1,59 ng/mL) comparing to non-CHF (1,05±0,26 ng/mL).Conclusion. Level of galectin-3 in MS patients is higher than in those non-MS, but in MS and CHF galectin-3 concentration is higher than nonCHF. Further elaboration on this relationship might be useful in improvement of CHD and MS diagnostics.